PENGARUH PENDIDIKAN DAN USIA IBU RUMAH TANGGA TERHADAP LITERASI KEUANGAN KELUARGA DI KELURAHAN BUKIT NENAS KOTA DUMAI - Siregar, Dina Fadilla; Gusnardi; Makhdalena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of education and age of housewives on family financial literacy in Bukit Nenas Village, Dumai City. This research uses a quantitative approach with primary data collected through questionnaires. The population consists of all housewives in Bukit Nenas Village totaling 1,727 individuals. The sampling technique used is simple random sampling, resulting in 95 respondents. Data analysis was conducted using multiple linear regression with the assistance of SPSS software, preceded by validity, reliability, and classical assumption tests. The results show that education has a positive and significant effect on financial literacy, particularly at the junior high school, senior high school, and higher education levels, while elementary education is not significant. Meanwhile, age does not entirely have a significant effect, as only the group aged over 50 years shows a positive and significant influence on financial literacy. Simultaneously, education and age affect financial literacy, with education being the more dominant factor.